Analysis of Brand Image, Product Innovation, and Word of Mouth on Purchasing Decisions Tekiro in Surabaya - Ainul Yaqin; Nuruni Ika Kusuma Wardani; Reiga Ritomea Ariescy (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of brand image, product innovation, and word of mouth on purchasing decisions of Tekiro in Surabaya. This study uses a quantitative method, namely by using 98 people as a research sample. The respondents were taken using a non-probability sampling method with a purposive sampling technique. The data collection method was carried out through the distribution of conventional questionnaires and was measured using a Likert scale. The analysis used is Partial Least Square (PLS). The results of this study indicate that brand image and word of mouth variables have a significant influence on purchasing decisions, but product innovation variables do not significantly influence purchasing decisions for Tekiro in Surabaya.